Comparison of the Diagnostic Value of Mentzer Index and RDW Index in the Screening of Beta Thalassemia Trait and Iron Deficiency Anemia (KYAMC Journal, 2025)
Background: Beta thalassemia trait is one of the common forms of hemoglobinopathies in Bangladesh. Individuals having beta-thalassemia trait have microcytic hypochromic anemia and asymptomatic course may be similar as that of iron deficiency anemia (IDA).So, it is important to differentiate between beta- thalassemia trait and non-thalassemia microcytosis as both conditions share common characteristics. Though the definitive diagnosis those patients of thalassemia trait is possible only by Hb-electrophoresis their certain blood indices which can differentiate between thalassemia trait and iron deficiency anemia. Mentzer index and RDW index are such index. Objectives: The aim of our study was to evaluate the reliability of Mentzer index and RDW index in the differentiation of iron deficiency anemia and beta thalassemia trait.Materials and Methods: This study was an observational study done on 120 patients. Only those patients who have been found to be having iron deficiency anemia by iron studies and cases of beta thalassemia trait who have been diagnosed by electrophoresis were included in this study. Those Patients who have received blood transfusion within 3 months study were excluded from the study. Mentzer index and RDW index of all the patients were calculated and the results were analyzed.Results: Mentzer index more than 13 presumed iron deficiency anemiaand less than 13 presumed thalassemia traits. Similarly, RDW index more than 220 presumed IDA and RDW index less than 220 presumed BTT are found to be reliable screening tool to differentiate in between iron deficiency anemia and thalassemia.Conclusion: Iron deficiency anemia and thalassemia trait can be reliably differentiated by Mentzer index and RDW index. In resource poor and developing countries like Bangladesh it can be used as screening tool.KYAMC Journal. 2024; 15(02): 73-76